2001
DOI: 10.1021/jo001112b
|View full text |Cite
|
Sign up to set email alerts
|

β-Trimethylsilyl Cyclopropylcarbenes

Abstract: Thermal decomposition of the in situ generated lithium salt of the tosylhydrazone derivative of cyclopropyl trimethylsilylmethyl ketone gave 1-cyclopropyl-1-trimethylsilylethylene, a product of exclusive silyl migration. Thermal decomposition of the sodium salts of tosylhydrazone derivatives of 1-trimethylsilylcyclopropyl alkyl ketones also gave methylenecyclopropane products derived from trimethylsilyl migration. These reactions were interpreted in terms of rapid trimethylsilyl migration to carbene-like cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Thus, we turned our attention to a silyl group, which is known to undergo a facile 1,2-migration to electron-deficient centers. Despite the well-known 1,2-Si migration to cationic centers,9,10 only little attention was devoted to 1,2-Si shifts to free-11 or metal-stabilized carbenes,12 especially with a focus on synthetic significance. Besides, scarce studies on migratory aptitudes in these systems have been reported 11,12…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we turned our attention to a silyl group, which is known to undergo a facile 1,2-migration to electron-deficient centers. Despite the well-known 1,2-Si migration to cationic centers,9,10 only little attention was devoted to 1,2-Si shifts to free-11 or metal-stabilized carbenes,12 especially with a focus on synthetic significance. Besides, scarce studies on migratory aptitudes in these systems have been reported 11,12…”
Section: Resultsmentioning
confidence: 99%
“…Hyperconjugative interactionsdefined as stereoelectronic interactions involving at least one σ orbitalare ubiquitous in chemistry and have profound effects on reactivity and conformational equilibria. A prominent example is the β-effect of silicon (or β-Si effect), where a R 3 Si substituent stabilizes positive charge at a position β to the silicon group, manifesting extraordinary rate accelerations, activation of typically inert functionalities , (e.g., C–H bonds), control over selectivity, and the isolation of typically high energy carbocation and carbene , species.…”
Section: Introductionmentioning
confidence: 99%
“…C. Computational Studies. Theoretical studies on the effect of bystander substituents on the reaction of carbenes have gained considerable attention. ,8b, Such studies have often been employed to rationalize the experimentally observed product distribution. Even though the effect of substituents on the mode of rearrangement in many cyclic carbenes has been studied, analogous studies with acyclic carbenes are not widely available.…”
Section: Resultsmentioning
confidence: 99%
“…Currently there is limited information available about the effect of β-heteroatoms on carbene reactivity. 1a,c, Specifically, only a few examples of (putative) β-hydroxycarbenes have been reported to date. , An acyclic β-hydroxycarbene, HOCH 2 −C−CH 3 , as generated thermally from a diazirine precursor, proceeds to rearrange exclusively via 1,2-H migration to generate propanal (Scheme a) 9a. Tomioka and Nunome reported the photochemical generation of a phenyl-substituted β-hydroxycarbene from the corresponding diazo precursor (Scheme b), and they observed an experimental 4:1 preference for alkyl (R) migration over O−H insertion and with no 1,3-C−H insertion 9b…”
Section: Introductionmentioning
confidence: 99%